Pelaksanaan Denda atas Nasabah Mampu Penunda Pembayaran Utang di Lembaga Keuangan Syariah - Alimin Alimin; Rizal Fahlefi (TSAQAFAH, 2020)
AbstractIslamic Financial Institutions (IFI) have business and social functions. One source of income for social funds other than infaq, shadaqah, and zakah is a fine fund for late payment of debt to able customers. This phenomenon is different from conventional financial institutions that make fines as one of their income. The fine at the IFI serves to discipline customers to pay debts, but the collection of these fines should not be done haphazardly because it can lead to ribawi practices and abuse of the situation. Decisions of various fatwa institutions have been made available regarding the rules for implementing this fine (DSN-MUI No. 17 of 2000 and the Sharia Standards of the AAOIFI Sharia Board of Bahrain No.8 and Majma 'al-Fiqh al-Islami Islamic Conference Organization No. 109 of 2000). Based on the results of this study it was found that the implementation of this fine was very varied. The study also found that the potential for these fines was quite large and would contribute positively to IFI's social functions while enhancing the positive image of the community. Variations in the application of these fines can be seen in terms of a) whether or not the fines are carried out with the aim of the promotion strategy, b) the amount of fines applied based on the effectiveness of the deterrence function, c) customer knowledge and understanding is still very low on these sanctions rules, and even IFI practitioners are still not optimally understood.Keywords: Sanction Fines, Usury, BMT, Capable Customers, Bad Debth, Islamic Financial Institutions.                                                     AbstrakLembaga Keuangan Syariah (LKS) mempunyai fungsi bisnis dan sosial. Salah satu sumber pemasukan dari dana sosial selain infak, sedekah dan zakat adalah denda keterlambatan pembayaran utang atas nasabah yang mampu. Hal ini berbeda dengan lembaga keuangan konvensional yang menjadikan denda sebagai salah satu pendapatan lembaga keuangan. Denda pada LKS tersebut berfungsi untuk mendisiplinkan nasabah terutang, namun dalam penerapan denda keterlambatan pembayaran tidak boleh dilakukan sembarangan karena dapat menjurus kepada praktik ribawi dan penyalahgunaan keadaan. Keputusan berbagai lembaga fatwa pun sudah ada tentang pelaksanaan denda ini (DSN-MUI No. 17 Th. 2000 dan Standar Syariah Dewan Syariah AAOIFI Bahrain No. 8 serta Majma' al-Fiqh al-Islami Organisasi Konferensi Islam No. 109 Th. 2000). Namun, berdasarkan hasil penelitian ternyata di lapangan terdapat berbagai variasi pelaksanaannya. Penelitian ini juga menemukan bahwa potensi denda tersebut cukup besar dan akan memberikan kontribusi positif bagi fungsi sosial LKS sekaligus meningkatkan kesan positif dari masyarakat. Variasi penerapan terlihat dari sisi a) dilaksanakan atau tidaknya denda tersebut dengan alasan strategi promosi, b)  jumlah denda yang diterapkan berdasarkan efektifnya tujuan penjeraan, c) pengetahuan dan pemahaman nasabah masih sangat rendah terhadap aturan sanksi ini, dan bahkan praktisi terhadap aturan sanksi ini masih belum maksimal.Kata Kunci: Denda Sanksi, Riba, BMT, Nasabah Mampu, Keterlambatan Pembayaran, Lembaga Keuangan Syariah.